2022
DOI: 10.3389/fpls.2022.883818
|View full text |Cite
|
Sign up to set email alerts
|

PanaxGDB: A Comprehensive Platform for Panax

Abstract: The genus Panax is a valuable natural medicinal source used worldwide that contains high levels of triterpenoid saponins with extensive pharmacological activities. In past decades, molecular biotechnology and breeding techniques have been respectively used to generate omics data and information on cultivars primarily from Panax ginseng (ginseng), Panax quinquefolium (American ginseng), and Panax notoginseng (Sanqi) to biosynthesize valuable saponins, improve product quality, and conduct cost-controlled cultiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…A total of 116 UGT s from P. notoginseng were obtained from the PanaxGDB database 1 ( Lin et al, 2022 ). According to previous studies, UGTs that catalyze dammarane-type ginsenoside belong mainly to the UGT 74, 94, and 71 families.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 116 UGT s from P. notoginseng were obtained from the PanaxGDB database 1 ( Lin et al, 2022 ). According to previous studies, UGTs that catalyze dammarane-type ginsenoside belong mainly to the UGT 74, 94, and 71 families.…”
Section: Resultsmentioning
confidence: 99%
“…fungi provide nutrients for the growth and development of G. elata tuber and obtain nutrients from it ( Xu, 2013 ). The bilateral flow of nutrients is the material basis of symbiotic partnerships between G. elata and fungi ( Liu et al, 2024 ). Xu et al isolated M. osmundicola from the protocorms of G. elata and confirmed that the fungi can effectively increase G. elata seed germination to up to 70% ( Xu et al, 1980 , Xu & Guo, 1989 ).…”
Section: How Does Orm Benefit Host Plants?mentioning
confidence: 99%
“…In the Panax genus, 13 Panax species were identified (accessed on 17 April 2023 from http://www.theplantlist.org). Some Panax species have a long history of use in traditional medicine due to their composition and functionality [1]. Korean ginseng (Panax ginseng) is considered one of the most precious medicinal plants, owing to the abundance of ginsenosides of highly economical and medicinal value; however, this form of ginseng also contains additional potentially useful secondary compounds, including polysaccharides, proteins, peptides, amino acids, polyphenols, polyacetylenes, alkaloids, lipids, essential oils, phytosterols, organic acids, and terpenes [2][3][4][5][6][7].…”
Section: Introduction Ginseng and Ginsenosidesmentioning
confidence: 99%
“…Many such compounds, including caffeic acid, vanillic acid, coumaric acid, ferulic acid, gentisic acid, cinnamic acid, and polyactetylenes, have been reported to possess biological and pharmacological activity as antioxidants, anti-inflammatory, and/or anticancer agents [ 2 , 4 , 8 , 9 , 10 ]. P. ginseng has been utilized to investigate various pharmaceutical applications, including use as antioxidants, anticancer, anti-inflammatory, anti-hyperglycemic, treating cardiovascular and cerebrovascular diseases, and boosting the immune system [ 1 , 2 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%